2010
DOI: 10.1016/j.alcr.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of pathways to adulthood in France: Evidence from a holistic approach

Abstract: International audienceYouth is often depicted as a transition from childhood to adulthood in the familial, residential and occupational domains. This approach brings in the idea of thresholds, such as leaving the parental home, getting married, having a first child or having a stable job. In practice, it has the advantage of allowing relatively simple comparisons of pathways to adulthood in time and space. However the study of thresholds has several limitations. First, it masks the problem of the reversibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 34 publications
(42 reference statements)
2
38
0
9
Order By: Relevance
“…This makes OM a quite natural choice. Today, OM is the most commonly used metric in studies on the transition to adulthood (Aassve, Billari & Piccarreta, 2007;Brzinsky-Fay, 2007;Robette, 2010). Second, preliminary analyses showed that in this particular illustration, the OM metric clearly outperformed other metrics.…”
Section: Sequence Analysismentioning
confidence: 99%
“…This makes OM a quite natural choice. Today, OM is the most commonly used metric in studies on the transition to adulthood (Aassve, Billari & Piccarreta, 2007;Brzinsky-Fay, 2007;Robette, 2010). Second, preliminary analyses showed that in this particular illustration, the OM metric clearly outperformed other metrics.…”
Section: Sequence Analysismentioning
confidence: 99%
“…There are, however, no clear expectations regarding the types of partnership trajectories individuals experience during the transition to adulthood or how individual characteristics relate to experiencing a specific type of partnership trajectory. Robette (2010) and Widmer and Ritschard (2009) provide contradictory evidence in their studies on gender differences in the de-standardization of life courses. It has furthermore rarely been studied how the turbulence of partnership histories and individual characteristics are interlinked (Widmer and Ritschard 2009).…”
Section: Theory and Empirical Evidencementioning
confidence: 99%
“…In a sequence analysis of the 2002 retrospective biographical survey of the Swiss Household Panel, Widmer and Ritschard (2009) find that cohabitational trajectories -that is, whether individuals live with their parents, children, or partner -are not mainly influenced by gender differences. However, Robette (2010), in a sequence analysis of the French Familles et Employeurs survey from [2004][2005], shows that women's pathways to adulthood are more dissimilar and more turbulent than men's. In their study of mothers and children from the Detroit metropolitan area, Xie et al (2003) calculate the individual probability of choosing marriage over cohabitation depending on women's earnings.…”
Section: Theory and Empirical Evidencementioning
confidence: 99%
“…(Casal et al 2006;Moreno et al 2012;Ulrich 2008;Vielra y Miret 2010;Urcola 2003). En definitiva, una perspectiva de transición o itinerario hacia la vida adulta que aglutinaría estructura, acción e historia, un modelo de análisis holista, pero que presenta limitaciones en tanto no tiene en cuenta la reversibilidad de los acontecimientos e incluso su no ocurrencia (Robette 2010;Iacovou 2011) Hace medio siglo, para la gran mayoría de los hombres, ser adulto o terminar la etapa de la juventud implicaba casarse, tener un empleo que le permitiera mantener a los hijos y a la mujer, y una vivienda. En la mayoría de los casos la institución del matrimonio era la norma.…”
Section: Introductionunclassified